Easily fabricated and lightweight PPy/PDA/AgNW composites for excellent electromagnetic interference shielding. Issue 46 (16th November 2017) - Wang, Yan; Gu, Fu-qiang; Ni, Li-juan; Liang, Kun; Marcus, Kyle; Liu, Shu-li; Yang, Fan; Chen, Jin-ju; Feng, Zhe-sheng
Abstract : Conductive polymer composites (CPCs) containing nanoscale conductive fillers have been widely studied for their potential use in various applications. Abstract : Conductive polymer composites (CPCs) containing nanoscale conductive fillers have been widely studied for their potential use in various applications. In this paper, polypyrrole (PPy)/polydopamine (PDA)/silver nanowire (AgNW) composites with high electromagnetic interference (EMI) shielding performance, good adhesion ability and light weight are successfully fabricated via a simple in situ polymerization method followed by a mixture process. Benefiting from the intrinsic adhesion properties of PDA, the adhesion ability and mechanical properties of the PPy/PDA/AgNW composites are significantly improved. The incorporation of AgNWs endows the functionalized PPy with tunable electrical conductivity and enhanced EMI shielding effectiveness (SE). By adjusting the AgNW loading degree in the PPy/PDA/AgNW composites from 0 to 50 wt%, the electrical conductivity of the composites greatly increases from 0.01 to 1206.72 S cm −1, and the EMI SE of the composites changes from 6.5 to 48.4 dB accordingly (8.0–12.0 GHz, X-band). Moreover, due to the extremely low density of PPy, the PPy/PDA/AgNW (20 wt%) composites show a superior light weight of 0.28 g cm −3 . In general, it can be concluded that the PPy/PDA/AgNW composites with tunable electrical conductivity, good adhesion properties and light weight can be used as excellent EMI shielding materials.